Pendidikan Anak Berkebutuhan Khusus Pada Down Syndrome - Mardhia, Annisa Radhiatun; Pransista, Nadia (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The importance of education for children does not apply only to children in general, but equally important for children with special needs Down syndrome. Special education is given to students who during the learning process experience difficulties due to physical obstacles, emotional disorders, mental disorders. For this reason, it is important to review the literature on Education for Children with Special Needs Down Syndrome. The method used in this research is Systematic Literature Review (SLR), which is a planned review activity to answer research questions carried out systematically and explicitly to identify, select and critically evaluate the results of previous studies, with six stages in the SLR method, namely: (1) planning (determining the object of research); (2) literature search; (3) assessment of inclusion and exclusion criteria; (4) quality assessment; (5) data collection; (6) data analysis. The results of this study, namely Down Syndrome (DS) or mongoloid children are a condition in which additional genetic material causes delays in child development, and sometimes refers to mental retardation. Down syndrome has a great influence on child development, both from cognitive development, language development, motor development, sensory development, to social development. In the education of children with Down syndrome, appropriate strategies and methods are needed during learning to improve their psychological skills, using a holistic approach that pays attention to cognitive, social, and emotional aspects.